Effect of Eleutherine americana Merr. bulb extract on blood pressure and heart rate in anesthetized hypertensive rats - Yori Yuliandra; Rizki Oktarini; Armenia Armenia (Fakultas Farmasi Universitas Andalas, 2018)
The effect of ethanolic extract of Eleutherine americana Merr. on the blood pressure and heart rate has been investigated. A number of 25 Sprague-Dawley male rats were induced with prednisone 1.5 mg/kg in combination with saline solution 2.5% for 14 days to obtain hypertension model. The rats were anesthetized and prepared for the recording of blood pressure and heart rate. The rats were divided into five groups receiving 100, 200, and 400 mg/kg of the extract, vehicle control, and captopril 30 mg/kg as the reference. The treatment was administered three times with 30 minutes interval. The systolic (SBP), diastolic (DBP), mean arterial pressure (MAP), and heart rate (HR) were recorded. The data were analyzed with two-way analysis of variance (ANOVA) followed by Duncan’s MRT (95% confidence interval). The study revealed that the extract exhibited a blood pressure lowering effect. The best antihypertensive activity of the extract was shown by the dose of 100 mg/kg. Meanwhile, HR was also affected inversely by the treatment, in which the lowest dose caused the highest increase. The study suggests that the extract of Eleutherine americana exhibits antihypertensive activity that may be potential for future development of drugs.